A smoke-free medical campus in Jerusalem: data for action. Issue 1 (December 2016) - Feldman, Itamar; Donchin, Milka; Levine, Hagai
Abstract Background Establishing smoke-free environments is a major component of tobacco control policy. The introduction of a smoke-free policy in medical campuses may serve as a role model for other educational and health institutions but little has been published about their prevalence or impact. In 2012, the Faculty of Medicine at Hebrew University–Hadassah in Jerusalem, Israel launched a smoke-free Medical Campus initiative. This study examined smoking behaviours, cigarette smoke exposure and attitudes towards the smoke-free campus policy among students and employees. Methods Using a self-administered questionnaire, data was collected from medical, dental and pharmacy students, as well as employees of the school of pharmacy. We approached the entire target population in 2013 (N  = 449), with a response rate of 72.5 % (N  = 313). Results The rate of smoking was 8.3 % (95 % CI 5.5–11.9 %). Most participants reported daily exposure or exposure several times a week to cigarette smoke (65.8 %). Overall, 98.0 % had reported seeing people smoke in open campus areas and 27.2 % indoors. Most participants supported the smoking ban inside buildings (94.2 %) but fewer supported (40.8 %) a complete ban of smoking throughout the campus, including outside areas. Only 18.4 % agreed that a policy prohibiting smoking was unfair to smokers. A multivariable analysis showed that support for a complete ban on smoking on campus was higher among non-smokers than for smokers (OR = 9.5, 95 % CI 2.2–31.5, p  = 0.02). Conclusions The smoke-free policy does not have total compliance, despite the strong support among both students and employees for a smoke-free medical campus. The data collected will assist policy makers move towards a total smoke-free medical campus and will aid tobacco control efforts in Israel and other countries.